التجاوز على المرافق العامة في القانون العراقي (بحث ميداني ضمن حدود أمانة بغداد) - المالكي, هادي نعيم; الراشدي, إسراء فاضل (Journal of Legal Sciences, 2019)
position The problem of the deterioration of public utility services belonging to municipal departments and frequent abuses, located on one of the biggest problems of the Iraqi citizen, the show in the capital Baghdad is more than other provinces, and that was a weakness of state authority secretions and mismanagement that resulted in weakness in the performance of Municipal districts of the provisions legislated legal protection to keep public money.The researcher reached to the existence of a number of gaps in the municipal legislation, Iraqi legislator was not in a number of successful legislation to preserve the sanctity of the public interest, Some texts have been wasted society's right of reprisal against the perpetrator, that by approving compensation in kind or financial support to the transgressor or give him the land transgressor him, which encouraged it to continue violating the sanctity of public property, In addition to contradict some of the legislation among them, some texts emphasizes the removal of abuses and punishes transgressor and employee negligent in removing it. Others ordered to wait and compensate squatters, and this is what made the work of the municipal districts confounded.The study was diagnosed with the most important of these texts in order to draw attention to the need for the Iraqi legislature to explain his reaction to the phenomenon of the abuses and work to enact a law that combines disparate texts and helps the municipality to stand firm to reduce this negative phenomenon.